Hydrogenation of benzene-toulene-xylene fraction of coke-chemical production for a preparation of ecologically pure high octane component for vehicle gasoline - Гуцуляк, Д.О.; Кочірко, Б.Ф.; Бойченко, С.В. (Proceedings of National Aviation University (archive), 2005)
Process for a hydrogenation of benzene-toulene-xylene fraction of coke-chemical production for a preparation of ecologically pure high octane component for vehicle gasoline has been described. Based on the results obtained, optimal conditions for carrying out the process were recommended.